Endothelia-targeting protection by Escin in decompression sickness rats - Zhang, K.; Jiang, Z.; Ning, X.; Yu, X.; Xu, J.; Buzzacott, Peter; Xu, W. (Nature Publishing Group, 2017)
© The Author(s) 2017. Endothelial dysfunction is involved in the pathogenesis of decompression sickness (DCS) and contributes substantively to subsequent inflammatory responses. Escin, the main active compound in horse chestnut seed extract, is well known for its endothelial protection and anti-inflammatory properties. This study aimed to investigate the potential protection of escin against DCS in rats. Escin was administered orally to adult male rats for 7 d (1.8 mg/kg/day) before a simulated air dive. After decompression, signs of DCS were monitored, and blood and pulmonary tissue were sampled for the detection of endothelia related indices. The incidence and mortality of DCS were postponed and decreased significantly in rats treated with escin compared with those treated with saline (P < 0.05). Escin significantly ameliorated endothelial dysfunction (increased serum E-selectin and ICAM-1 and lung Wet/Dry ratio, decreased serum NO), and oxidative and inflammatory responses (increased serum MDA, MPO, IL-6 and TNF-a) (P < 0.05 or P < 0.01). The results suggest escin has beneficial effects on DCS related to its endothelia-protective properties and might be a drug candidate for DCS prevention and treatment.